Scavenger receptor class B type I knockout mice develop extensive diet-induced coronary artery atherosclerosis in an age-dependent manner. - Samuel K Lee; Ting Xiong; Alexander S Qian; Jeong-Ah Yoo; B Sumayyah H Sokeechand; Mark T Fuller; Peter L Gross; Richard C Austin; Suleiman A Igdoura; Bernardo L Trigatti (PLoS ONE)
Objective Homozygous knockout of scavenger receptor class B type I (SR-B1) in mice with atherogenic mutations (such as knockout of the apolipoprotein E or low density lipoprotein receptor genes) results in spontaneous or diet-induced coronary heart disease characterized by atherosclerosis development in the aortic sinus and coronary arteries, platelet accumulation in coronary artery plaques, myocardial fibrosis, and early death. However, the extent of coronary artery atherothrombosis and myocardial fibrosis in mice lacking SR-B1 alone (homozygous SR-B1 knockout mice) has not been examined. Although age is a major risk factor for coronary artery disease, few studies directly examine the effects of age on susceptibility to atherosclerosis or coronary artery atherothrombosis and myocardial fibrosis in mice. Therefore, we set out to examine the effects of age on diet-induced atherosclerosis in female homozygous SR-B1 knockout mice. Approach and results SR-B1 knockout mice exhibited little-to-no aortic sinus or coronary artery atherosclerosis at 52 weeks of age, when fed a normal diet. However when fed a high-fat, high-cholesterol, cholate-containing (HFCC) diet for 12 weeks from either 14 weeks of age (26-week-old at analysis) or 40 weeks of age (52-week-old at analysis), they developed similar degrees of atherosclerosis in their aortic sinuses. Interestingly, the older aged SR-B1 knockout mice exhibited increased coronary artery atherosclerosis, increased vascular cell adhesion molecule 1 levels and platelet accumulation in coronary arteries, and increased myocardial fibrosis and plasma levels of cardiac troponin I compared to the younger aged mice. Older-aged HFCC diet-fed SR-B1 knockout mice also exhibited reduced survival to humane endpoint. Moreover, older-aged HFCC diet-fed SR-B1 knockout mice exhibited a greater inflammatory state with increased levels of circulating interleukin-6, tumour necrosis factor alpha, and neutrophils, despite plasma lipid levels being unchanged. Consistent with the increased circulating neutrophils, older-aged HFCC diet-fed SR-B1 knockout mice exhibited increased accumulation of the neutrophil marker myeloperoxidase and increased neutrophil extracellular traps in atherosclerotic plaques in the aortic sinus and increased abundance of atherosclerotic coronary arteries containing neutrophil extracellular traps. Conclusions HFCC diet-fed homozygous SR-B1 knockout mice develop occlusive coronary artery atherothrombosis and myocardial fibrosis in an age-dependent manner, and exhibit an increased inflammatory state with older age. Therefore, aged SR-B1 knockout mice may prove to be an attractive mouse model to analyze age-dependent mechanisms associated with coronary artery disease development, which may facilitate the discovery of more effective therapeutics to treat cardiovascular disease.